2004
DOI: 10.1103/physreve.69.016108
|View full text |Cite
|
Sign up to set email alerts
|

Multilane simulations of traffic phases

Abstract: The optimal velocity model, as modified by the author, is used in simulations of traffic on a dual-lane highway and a single-lane highway with an on-ramp. The equilibrium solutions of the modified model cover a two-dimensional region of flow-density space beneath the fundamental-diagram curve, rather than just lying on the curve as in the original model. Thus it satisfies a requirement of the three-phase model of Kerner [Phys. Rev. Lett. 81, 3797 (2002)]. Synchronization of velocity across dual lanes due to fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…There also exist multi-species models (Mason & Woods 1997;Nagatani 2000) where drivers with different characteristics are considered, that is, g, f , , t, s, k → g n , f n , n , t n , s n , k n is assumed, which may be different for each n. However, usually only two different species are mixed, corresponding to automobiles and trucks. One might also extend car-following models to make them capable of modelling multi-lane traffic or junctions, in which case lane changes need to be handled (Davis 2004;Kesting et al 2007). Indeed, when a lane change occurs, the right-hand side of model (3.8) or (3.10) changes, that is, one needs to deal with a 'discontinuous dynamical system'.…”
mentioning
confidence: 99%
“…There also exist multi-species models (Mason & Woods 1997;Nagatani 2000) where drivers with different characteristics are considered, that is, g, f , , t, s, k → g n , f n , n , t n , s n , k n is assumed, which may be different for each n. However, usually only two different species are mixed, corresponding to automobiles and trucks. One might also extend car-following models to make them capable of modelling multi-lane traffic or junctions, in which case lane changes need to be handled (Davis 2004;Kesting et al 2007). Indeed, when a lane change occurs, the right-hand side of model (3.8) or (3.10) changes, that is, one needs to deal with a 'discontinuous dynamical system'.…”
mentioning
confidence: 99%
“…The figure shows that the numerical results are in good agreement with the analytical results. It is instructive to present the inequality (28), which separates the regimes of stabilization and destabilization of the free flow in the physical variables. In these variables inequality (28) takes the form…”
Section: Uniform Flowmentioning
confidence: 99%
“…Quite recently studies appeared on traffic flows with vehicles that possess a control system trying to keep a desired headway: vehicles with adaptive cruise control (ACC) [22][23][24][25][26]. Several microscopic models have been proposed to model the ACC vehicles [22,27,28]. It was shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have shown that if 30% of vehicles had ACC, the formation of jams in heavy traffic could be eliminated [1][2][3][4][5][6][7][8][9][10]. The ACC vehicles are assumed to be governed by control parameters that give string stability [11].…”
Section: Introductionmentioning
confidence: 99%